Expression plasticity and evolutionary changes extensively shape the sugar‐mimic alkaloid adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects. Issue 13 (4th June 2018) - Li, Xiaotong; Shi, Liangen; Dai, Xiangping; Chen, Yajie; Xie, Hongqing; Feng, Min; Chen, Yuyin; Wang, Huabing
Abstract: During the co‐evolutionary arms race between plants and herbivores, insects evolved systematic adaptive plasticity to minimize the chemical defence effects of their host plants. Previous studies mainly focused on the expressional plasticity of enzymes in detoxification and digestion. However, the expressional response and adaptive evolution of other fundamental regulators against host phytochemicals are largely unknown. Glucosidase II (GII), which is composed of a catalytic GIIα subunit and a regulatory GIIβ subunit, is an evolutionarily conserved enzyme that regulates glycoprotein folding. In this study, we found that GII α expression of the mulberry‐specialist insect was significantly induced by mulberry leaf extract, 1‐deoxynojirimycin (1‐DNJ), whereas GII β transcripts were not significantly changed. Moreover, positive selection was detected in GIIα when the mulberry‐specialist insects diverged from the lepidopteran order, whereas GIIβ was mainly subjected to purifying selection, thus indicating an asymmetrically selective pressure of GII subunits. In addition, positively selected sites were enriched in the GIIα of mulberry‐specialist insects and located around the 1‐DNJ‐binding sites and in the C‐terminal region, which could result in conformational changes that affect catalytic activity and substrate‐binding efficiency. These results show that expression plasticity and evolutionary changes extensively shape sugar‐mimic alkaloids adaptation of nondigestive glucosidase in lepidopteran mulberry‐specialist insects. Our study provides novel insights into a deep understanding of the sequestration and adaptation of phytophagous specialists to host defensive compounds.